Technical and economic study of striking and clearing operations in buildings under construction. Case study in Bogotá, Colombia (2016)
This paper evaluates the economic benefits of shorter construction times that can be attained by applying the New Simplified Procedure (NSP) in multi-storey buildings. The reference building was a multi-storey residential reinforced concrete framework structure with one-way slabs located in Bogotá, Colombia. The study was divided into different phases including the characterization of the components, a study of the different methods to determine load transmissions between slabs and shores, and a review of the cost of renting shoring and formwork materials and labor costs for the building under study. After applying the procedure, an economic assessment was carried out on the execution times obtained in each of the operations studied. The analysis of the construction process of the building structure using the NSP showed that considerable savings can be achieved in construction times without any risk for the integrity of the structure.